Study of Investors’ Preference for the Selection of an Insurance Product - Pradnya Gugale; Prof. Vedashree Mali (International Journal of Engineering and Management Research, 2021)
Human Being’s life is the most significant asset and life-insurance is the most significant sort of insurance which gives financial protection to theindividualhimself/herself and to his family at the hour of dubious dangers or harm. Life insurance gives both safety and protection to people and furthermore encourages investment funds among individuals. The present exploratory based investigation was chosen with a target to analyze those factors which impact client’s strategy purchasing choice and furthermore examine the inclinations of clients while making decision about insurance policy investment. Different insurance-related factors have been examined in the paper. Also, the said study has been conducted to know the satisfaction level of the clients and also to know the benefit they have been receiving from the company (if any). The information for the research has been gathered from primary data. The study zone is restricted to Maharashtra state and the test sample is 30 investors. The hypotheses have been based on the basis of demographic and the factors related to the insurance-based preference.factors and tested the same with the help of statistical tool T-test. The analyzed data had been produced in the form of a tables and graphs/charts. Insurance agencies should spread more awareness about life insurance, a decrease in the premium amount, and giving more attention to need-based innovative products are a portion of the recommendations which I would suggest. The paper closes with the segment that factors of the individuals play a significant and essential role in choosing the purchase of insurance policies.